2013
DOI: 10.1177/1933719113477483
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Pathways Involved in 2-Methoxyestradiol Synthesis and Their Role in Preeclampsia

Abstract: Preeclampsia (PE) remains a major cause of maternal/fetal morbidity-mortality worldwide. The first stage of PE is characterized by placental hypoxia due to a relative reduction in uteroplacental blood flow, resulting from restricted trophoblast invasion. However, hypoxia is also an essential element for the success of invasion. Under hypoxic conditions, 2-methoxyestradiol (2-ME) could induce the differentiation of cytotrophoblast cells into an invasive phenotype in culture. 2-Methoxyestradiol is generated by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 86 publications
1
23
0
Order By: Relevance
“…In addition, the circulating level of an estrogen metabolite, 2-methoxyestradiol (2-ME), is significantly upregulated in normal pregnant women, as compared with nonpregnant women. However, plasma levels of 2-ME are significantly reduced in women with preeclampsia [35]. This is consistent with animal studies that demonstrated that a deficiency in catechol-O-methyl transferase, and a subsequent reduction in 2-ME concentration, resulted in the development of preeclampsia-like signs [36].…”
Section: Discussionsupporting
confidence: 77%
“…In addition, the circulating level of an estrogen metabolite, 2-methoxyestradiol (2-ME), is significantly upregulated in normal pregnant women, as compared with nonpregnant women. However, plasma levels of 2-ME are significantly reduced in women with preeclampsia [35]. This is consistent with animal studies that demonstrated that a deficiency in catechol-O-methyl transferase, and a subsequent reduction in 2-ME concentration, resulted in the development of preeclampsia-like signs [36].…”
Section: Discussionsupporting
confidence: 77%
“…Consequently, the transformation of spiral arteries is suppressed, and instead of high‐resistance, low‐flow vessels, they are transformed into dilated vessels . The decreased blood flow and fetoplacental perfusion induce placental ischemia, producing the subsequent oxidative stress and angiogenic imbalance that contribute to the development of endothelial dysfunction in the later gestation period of PE patients . In the present study, JEG‐3 cell invasion ability increased with elevated RBP4 concentration.…”
Section: Discussionmentioning
confidence: 46%
“…With COMT being responsible for methylating 2-Hydroxyestradiol (2-HE) into 2-ME, it has been proposed that the low activity or expression of this enzyme could be involved in the pathogenesis of PE. The normal expression of COMT in placentae of patients with PE [11] and the conflicting results regarding the presence of SNPs that may reduce the activity of this enzyme in these patients [10] force us to search other explanations [12]. The Methionine-homocysteine metabolism (MHM), the process responsible for supplying COMT with the methyl group necessary for 2-ME synthesis, could be an alternative if it is somehow altered, being unable to supply enough methyl groups to sustain adequate concentrations of 2-ME.…”
Section: Introductionmentioning
confidence: 99%